The meaning of religious symbolic signs in children’s clothing as souvenirs from Ampel Village, Surabaya - Rahayu, Genduk Ayu Sugma; Aji, Restu Ismoyo; Sutejo, Aris (Universitas Indraprasta PGRI, 2026)
This study aims to analyze the meaning of religious symbols used in children’s clothing as souvenirs from Ampel, Surabaya. Nearly all of the symbols have undergone a long process of acculturation, through which they have acquired the religious meanings recognized today. The problem addressed in this study is whether these symbols still retain their religious meanings and to what extent their meanings have shifted. This study analyzes children's clothing as the research object and uses Roland Barthes’ visual semiotics framework as the method due to its compatibility in examining symbolic signs at the level of denotation, connotation, and myth. The results of this study demonstrate that the Ampel gate, gold color, and typography function as specific semiotic elements that construct layered meanings related to sacred space, cultural hybridity, and commodification. The symbols remain relevant; however, their meanings have shifted from purely spiritual representations to visual forms shaped by tourism consumption. This study is recommended to serve as the foundation for developing knowledge in tourism souvenir design that represents religious meaning more critically and contextually.